EVOLUTION OF TEACHING METHODS IN 21st-CENTURY PEDAGOGY: FROM TRADITION TO INNOVATION - Fatkullaeva Viktoriya Saifullaevna (Modern American Journals, 2025)
The article examines the process of the evolution of teaching methods in the pedagogy of the 21st century, from traditional approaches to innovative ones. The article examines the origins of traditional methods, the main directions of modernization of educational technologies, as well as the role of the teacher in an innovative environment. It is shown that the modern educational process requires the integration of classical and innovative teaching methods.
Keywords: Pedagogy of the 21st century, innovative teaching methods, traditional methods, digitalization of education, facilitator, project-based learning, flipped classroom.